In Silico Compounds Analysis in Ginger (Zingiber Officinale) as Candidate for Acute Coronary Syndrome Medication - James Ibrahim; Dian Ratih Laksmitawati; Esti Mulatsari; Esti Mumpuni (PT FORMOSA CENDEKIA GLOBAL, 2023)
Based on the World Health Organization and other authorized health organizations, heart disease is one of the diseases with the largest contributor to death in the world, including Acute Coronary Syndrome with an estimated number of patients of 126 million in 2020. This research entails phytoconstituents of Zingiber officinale as possible Acute Coronary Syndrome medication with in silico methods by altering the activity of HMG-CoA Reductase, PPAR-α, PPAR-γ, NPC1L1, β1-AR, ACE and P2Y12R. This research used Molegro Virtual Docker 6.0 as tool to analyze the compounds with docking computation approach and also utilize Protein Data Bank (PDB) files : 1HWK, 2ZNN, 4EMA, 4AMJ, 2YDM, 4PXZ and 7DFZ. Chemdraw 3D was used in order to minimize the ligand’s energy. Furthermore, to analyze the pharmacokinetics aspects, this study involved pkCSM and SwissADME to predict a few parameters in each aspect, and finalized the research with Dynamic Molecular approach with YASARA.